METODE DEMONSTRASI DALAM PEMBELAJARAN IPA: STUDI KUALITATIF TERHADAP MINAT BELAJAR PESERTA DIDIK KELAS IV - Kaisari, Dona; Achmad, Firdaus; Setyaningrum, Vidya (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research aims to arouse students' interest in learning through demonstration methods in science subjects. The type of research used is field research with a descriptive analysis method throught a qualitative approach. The data sources in this research are class IV teachers and class IV students. Collection techniques and tools use interview techniques with semi-structured interview guidelines, and observation techniques use observation sheets, while documentation techniques use check list guidelines, photos and so on. Data analysis techniques use data reduction, data presentation, and data verification. Data validity testing techniques use source triangulation and data triangulation. The results of the research show that: (1) Teachers' understanding of the demonstration method in science subjects is quite understanding of the application of the demonstration method; (2) The steps taken by the teacher in implementing the demonstration method are quite good in the science learning process; (3) Students' interest in learning increased after implementing the demonstration method, namely 22 students. So it can be concluded that the demonstration method can arouse students' interest in learning in science subjects with energy source material.